2019
DOI: 10.3389/fimmu.2019.01017
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity and Memory T Cell Subset Distribution of in vitro-Stimulated CD8+ T Cells Specific for HER2/neu Epitopes

Abstract: Minimal residual disease remaining after resection of primary tumors can lead to tumor recurrence and metastasis, increasing mortality and morbidity rates among cancer patients. Thus, there is a need for new technologies for recognition and elimination of single cancer cells remaining in a patient's body after radiation therapy, chemotherapy, or surgical resection. Effector CD8 + T cells, also commonly known as cytotoxic T lymphocytes (CTLs), play a key role in antitumor cellular immunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 52 publications
1
18
0
1
Order By: Relevance
“…CD8 + T cells play an essential role in anti‐tumour immunity and can effectively kill tumour cells using CTL function. In addition, CD4 + T cell activity is indispensable for cytotoxicity . We then determined whether hesperetin as an adjuvant enhanced the immune response of CD4 + T lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD8 + T cells play an essential role in anti‐tumour immunity and can effectively kill tumour cells using CTL function. In addition, CD4 + T cell activity is indispensable for cytotoxicity . We then determined whether hesperetin as an adjuvant enhanced the immune response of CD4 + T lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CD4 + T cell activity is indispensable for cytotoxicity. 24 We then determined whether hesperetin as an adjuvant enhanced the immune response of CD4 + T lymphocytes. We stained for cytokines including IL-4 and IFN-γ, and found that, compared to vaccination with inactivated B16F10 antigen alone, inactivated B16F10 antigen plus HES stimulated high levels of cytokine secretion ( Figure 3A).…”
Section: T Lymphocyte Immune Response Increased By Hesmentioning
confidence: 99%
“…A positive correlation was observed in multiple studies between the number of tumor infiltrating cytotoxic CD8+ T cells and clinical outcome in BC that may improve patient survival. 24,37,46,60,62 Decreased number of tumor infiltrating CD8+ T cells in BC was significantly associated with lymph node metastasis and a higher disease stage. These results suggest that cytotoxic CD8+ T cells are heavily involved in antitumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was observed in multiple studies between the number of tumor infiltrating cytotoxic CD8+ T cells and clinical outcome in BC that may improve patient survival [13,26,36,41].…”
Section: Cd8+ T Lymphocytes and Cd4+ T Helper Cells May Promote Tumormentioning
confidence: 93%